The model its formation of ecological competency of the future specialist of water transport is presented. - GURENKOVA, Olga (Continuing Professional Education: Theory and Practice, 2019)
The paper summarises approaches to determination of the term “competency”, “professional competency”. Based on this the role of ecological competency and its formation during study in the higher learning institution are determined. The model of ecological competency of the future specialist of water transport is presented